2005
DOI: 10.1038/ng1632
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tumor growth by altered stem-cell asymmetric division in Drosophila melanogaster

Abstract: Loss of cell polarity and cancer are tightly correlated, but proof for a causative relationship has remained elusive. In stem cells, loss of polarity and impairment of asymmetric cell division could alter cell fates and thereby render daughter cells unable to respond to the mechanisms that control proliferation. To test this hypothesis, we generated Drosophila melanogaster larval neuroblasts containing mutations in various genes that control asymmetric cell division and then assayed their proliferative potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
392
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(411 citation statements)
references
References 24 publications
13
392
0
6
Order By: Relevance
“…In this context, it is worth noting that symmetric divisions per se may induce aneuploidy, thus further contributing to cancer initiation. This is the case for Drosophila neuroblasts, which become aneuploid upon a few rounds of symmetric divisions [43], probably because the same machinery that controls the modality of SC division also regulates centrosome functions, mitotic spindle orientation and chromosome segregation [44,45]. Opinion…”
Section: Opinionmentioning
confidence: 99%
“…In this context, it is worth noting that symmetric divisions per se may induce aneuploidy, thus further contributing to cancer initiation. This is the case for Drosophila neuroblasts, which become aneuploid upon a few rounds of symmetric divisions [43], probably because the same machinery that controls the modality of SC division also regulates centrosome functions, mitotic spindle orientation and chromosome segregation [44,45]. Opinion…”
Section: Opinionmentioning
confidence: 99%
“…A further possibility is a mixture of symmetrical and asymmetrical cell divisions ( Figure 3C). Symmetrical stem cell divisions provide a mechanism to increase the stem cell population after stem cell loss, but symmetrical divisions can also lead to a dangerous escalation of stem cell numbers, as seen with disruption of asymmetrical neuroblast cell division in Drosophila melanogaster that leads to lethal, expansive, tumourlike lesions when such cells are transplanted into adult hosts [15]. Alternatively, lack of appropriate signalling can lead to stem cell exhaustion, as seen in mice lacking Tcf-4 and so unable to form β-catenin-Tcf-4 complexes essential for Wnt signalling in the small intestine ( Figure 4) [16].…”
Section: Self-renewal and The Stem Cell Nichementioning
confidence: 99%
“…Normally, Drosophila neuroblasts divide asymmetrically, a process which is controlled by genes regulating cell polarity and cell fate 106,107 . Using Drosophila as a model, three recent studies have shown that the loss of polarity and impairment of asymmetric division in stem cells leads to tumorigenesis [108][109][110] . In these reports, neuroblasts containing mutations in various genes that control cell division (Raps, Mira, Numb, Brat and Pros) developed aggressive tumors that could be retransplanted into new hosts.…”
Section: Asymmetric Division Of Stem Cells and Cancermentioning
confidence: 99%
“…In these reports, neuroblasts containing mutations in various genes that control cell division (Raps, Mira, Numb, Brat and Pros) developed aggressive tumors that could be retransplanted into new hosts. Importantly, asymmetric division was disrupted in mutant stem cells, whereby both daughter cells grow and behave like neuroblasts leading to the formation of tumors [108][109][110] . This transformation was associated with genome instability and centrosome alterations ( fig.…”
Section: Asymmetric Division Of Stem Cells and Cancermentioning
confidence: 99%